The College Type: Personality and Educational Inequality - Lundberg, Shelly (Journal of Labor Economics, 2013)
I examine the effects of cognitive ability and personality traits on college graduation in a recent cohort of young Americans, and how the returns to these traits vary by family background, and find very substantial differences across family background groups in the personality traits that predict successful completion of college, particularly for men. The implications are twofold. First, the returns to noncognitive traits may be highly context dependent. Second, policy discussion concerning educational inequality should include not just the possibilities for remediating the skill levels of poor children, but also approaches to changing the environments that limit their opportunities.